Development of Some Selected Stochastic Models of Human Fertility in India: The Untold Stories - Yadava, Ram Chandra (Journal of the Indian Institute of Science, 2022)
Modeling of any phenomenon requires the knowledge of the subject and the mathematical skill that is required to express the phenomenon in the form of mathematical relationship(s). In the process of model building, the researcher(s) experience several failures and learnings before getting the final model. While large number of final models are developed and published, learnings of model development are seldom documented. Hence, there is a need to bring such articles which could present the learning of model development. Under this premise, the author which has experience of developing stochastic models of human reproduction aims, in this article, to narrate those learnings which he had encountered in the development of large number of models. Since detailed descriptions of those models are already available in publications, the article would skips detail derivations of those models but to provide learnings of the development of the models.